'Times that by 100': Student learning from international practicum. (November 2018) - Hay, Kathryn; Lowe, Simon; Barnes, Gina; Dentener, Alex; Doyle, Rochelle; Hinii, Georgea; Morris, Hanah
International placements are uncommon for Aotearoa New Zealand social work students compared with many other countries. In 2015 five students undertook a 10-week placement in Cambodia. This article explores the students' perspectives on the skills, knowledge and capabilities required for international placements. The findings from this study indicate that questions remain as to whether the associated challenges outweigh the advantages of international placement experiences. We recommend that working with tertiary institutions from countries with more established international placement programmes may be one way of addressing some of the challenges and advancing international placements for Aotearoa New Zealand students.